5. COMPARISON OF THE ANALGESIC EFFECT OF CONTINUOUS ANAESTHESIA INFLATION WITH AUTOMATIC INTERVAL INJECTION OF SMALL DOSES (PIEB) IN EPIDURAL ANESTHESIA DURING LABOR (Vietnam Journal of Community Medicine, 2025)
Objective: To compare the pain relief effectiveness in labor of continuous anesthetic infusion method and automatic intermittent injection of small doses of anesthetic during epidural anesthesia.Methods: Randomized clinical description with comparison. 100 patients were randomly distributed into 2 equal groups. The patient received L3-4 epidural anesthesia. After a test dose of 8 ml Ropivacaine 0.1% with fentanyl 1µg/ml (divided into 2 times / 5 minutes). Group P (PIEB) 8ml injected into the spinal cavity each time (Lockout 60 minutes). Group C (CEI) was run continuously at 8ml/60 min. If the VAS score is ≥ 4, the patient injects 6 ml of anesthetic (PCA). If the patient still has a VAS score ≥ 4, give a rescue dose of 6ml of Lidocaine 1%. The bolus dose in group P: 15 minutes after electric syringe bolus (VAS ≥ 4). Bolus dose in group C: dose for continuous infusion with VAS ≥ 4. Evaluation: Time to anesthesia induction, VAS pain score, rescue dose, lidocaine (mg), ropivacaine (mg) and fentanyl (µg), patient satisfaction.Results: VAS scores at the time of cervical dilation, pushing stage, VAS at perineal stage and uterine control in group P were lower than in group C. Adding 1 rescue dose of group P (12%) was lower than that of group C (28%), Lidocaine group P (113.4 ±  33.6 mg) was lower than that of group C (128 ±  45.3 mg), Ropivacaine group P ( 47.8 ±  10.8 mg) was lower than that of group C (54.5 ± 11.4 mg), patient satisfaction in group P (96%) higher than group C (84%) with p < 0.05.Conclusions: VAS score of group P is lower than group C, rescue dose, amount of anesthetic of group P is lower than group C. Satisfaction of pregnant women in group P (96%) was higher than in group C (84%), a difference statistically significant with p < 0.05
Keywords: automated intermittent injection of small doses (PIEB); epidural anesthesia, labor